PENGARUH JOB INSECURITY, BURNOUT DAN ORGANIZATONAL JUSTICE TERHADAP TURNOVER INTENTION PEGAWAI BAGIAN OPERASIONAL PADA SATUAN POLISI PAMONG PRAJA KABUPATEN ROKAN HULU - Ria Diati Oktariana (Fakultas Ekonomi Universitas Pasir Pengaraian, 2021)
This study aims to determine the effect of job insecurity, burnout and organizational justice on employee employee turnover intention in the Civil Service Police Unit in RokanHulu Regency. The population in this study were all employees of the Civil Service PoliceOperational unit of Rokan Hulu Regency. The research sample used a purposive samplingtechnique, with a total of 79 people. The independent variables in this study were jobinsecurity (X1), burnout (X2), organizational justice (X3), dependent variable (Y) turnoverintention. Methods of data collection using observation, documentation and questionnaires.Data analysis uses multiple linear regression. Based on partial test results it is known that jobinsecurity, burnout and organizational justice have a significant effect on turnover intention,where the significant value indicates that it is smaller than the significant level of 0.05. Thecalculation of the coefficient of determination shows that the influence of job insecurity,burnout and organizational justice together has a positive effect on turnover intention of97.5%, while the remaining 2.5% is influenced by other variables not examined.